PRZESTĘPCZOŚĆ NIELETNICH W ŚWIETLE BADAŃ AKT SPRAW SĄDOWYCH A PROBLEM ODPOWIEDZIALNOŚCI RODZICÓW ZA SZKODY WYRZĄDZONE PRZEZ ICH DZIECI - Słyk, Jerzy (Zeszyty Prawnicze, 2017)
Juvenile Delinquency in the Light of the Examination of Court Files and the Problem of Parents’ Responsibility for Damages Caused by Their Children Summary The article presents the results of the empirical research made by the author in family and juvenile courts. The research encompassed 200 pages of court files, and its aim was to obtain information on the family situation, progress in education and the behaviour of the minors who caused a damage. The achieved results allowed to evaluate the causes of their behaviour as well as draw conclusions related to binding legal regulations concerning the problem of parents’ civil responsibility for the damage caused by their child.